PEDAGOGICAL CONDITIONS FOR THE IMPLEMENTATION OF INDIVIDUAL EDUCATION - Rozikova Lola Tuychiyevna (Journals Park Publishing, 2022)
The article emphasizes that currently ensuring the organization of the educational process based on individual learning technologies is one of the most urgent tasks. Learning technology-first, as a pedagogical technology means a range of procedural actions. It provides opinions about the guaranteed achievement of promising results within a set time, in the face of the variability of the educational process.
Keywords: competence; global Adventure; Global education